IMPLEMENTATION OF SOFT SYSTEM METHODOLOGY DEVELOPMENT OF A DECISION SUPPORT SYSTEM BASED ON THE INTERNET OF THINGS INTHE SUNFLOWER AGRO-INDUSTRY SUPPLY CHAIN - Nurhasanah, Nunung; Wajdi, Muhammad Raihan; Mudrikah, Isna Ibnah; Adhipramana, Ivan; Samijayani, Octarina; Adlina, Ginang Natilla; Muthohar, Akhmad; Alfathsyah, Arrasyid; Aribowo, Budi; Haryadi, Dody (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
Sunflower (Helianthus annuus L.) has the potential for high added economic value to be developed. Indonesia has the opportunity to develop a sunflower agro-industry which is processed into cooking oil. There has not been much research related to the sunflower agro-industry supply chain. A plan for improvements to the supply chain cannot yet be carried out, because the situation in the supply chain has not been comprehensively elaborated. Therefore, this research aimed to analyse the situational supply chain of the sunflower agribusiness. The method used was soft system methodology developed by Checkland. This research has succeeded in designing a conceptual model that produces two human activities, namely: 1) Development of production devices for the drying process of sunflower seeds based on the Internet of Things, (2) Utilization of the Blynk application to support the decisions on the sunflower agro-industry supply chain network, and (3) Development of the prototype digital platform decision support system on the production device based on internet of things. These three activities are also recommendations given as corrective actions to increase the productivity of the sunflower agro-industry. Recommended actions have also been successfully assessed through RE3IS. Future development of this research is to build a digital prototype of an internet of thongs-based decision support system platform that can be easily accessed by sunflower agro-industry managers. The stages in this research are still limited to the recommendation stage for corrective action. The implementation stage can be used as research development in the future. Apart from that, situational analysis is still limited to upstream and intermediate supply chain networks. Therefore, situational analysis of the downstream supply chain network can be carried out in the future. Keywords: cooking oil, internet of things, soft system methodology, sunflower seed, sunflower agro-industry supply chain